Scenes of Studio Practice - Christian Edwardes (Ambiances)
The creative turn within geography has seen a number of returns to the artists’ studio as a site for exploring the vital, immanent, and affective relations that form these spaces of creative practice. Where interviews, observations, collaborations, with artists have directed attention to the non-representational, this paper approaches the studio as both a scene, and an atmospheric staging. Taking up broader discourses around the scenographic, it argues that scenes not only take account of the durational and compositional construction of studio spaces, but can be understood as a form of training and attunement through which participants are enrolled in the joint composition of studio atmospheres and registers. It directs attention to the agency that these compositions have in the production of the studio imaginary.